GEOLOGI DAN STUDI DIAGENESIS BATUGAMPING FORMASI EEMOIKO DAERAH SAMBALAGI DAN SEKITARNYA, KABUPATEN MOROWALI, SULAWESI TENGAH - Khoirul Basyar, Ahmad
Sambalagi Village is a part of Morowali Regency, Central Sulawesi. Research area is located in forest zone of border Central Sulawesi and Southeast Sulawesi with 72 km2 of area of research within UTM 9649000 m – 9658000 m northing and 418000 m – 426000 m easting in zone 51S, WGS84. The purposes of this research are to know geological setting and the history. Others, limestone diagenetic study for reservoir characterization in oil and gas field in the area. The shape of river valley is dominated by “V” shape. Geomorphology of research area is a valley, ridges, and hills which are mostly caused by the lithology of rocks and geological structures seen from topography and rectangular and trellis river pattern which is identified in research area. There are two geomorphological unit which are Sambalagi Karst Hills Unit and Matarape Fault Hills Unit. The lithology of research area characterized by sedimentary rocks of Mollase Sulawesi like sandstone and mudstone which have deposited shallow marine environment (Langkowala Formation), limestone (Eemoiko Formation), and conglomerate which have deposited in alluvial environment (Pandua Formation). They have deposited since Middle Miocene. Geological structures of research area driven by simple shear mechanism which are formed strike-slip fault and folds. Trend of strike planes shows northwest – southeast direction. Diagenetic proses have seen in clastic limestone in Eemoiko Formation. Limestone porosity ranged between 1% - 3%. In short, diagenetic in Eemoiko Formation starts with marine phreatic, burial, mixing zone, meteoric phreatic, and the last meteoric vadose.